Prophylactic progesterone prevents adverse behavioural and neurocognitive effects of neonatal anaesthesia exposure in rat. (February 2022) - Wali, Bushra; Sayeed, Iqbal; Stein, Donald G.; Raper, Jessica
Abstract: Background: Evidence from animal models and human studies suggests an association between early general anaesthesia exposure and development of long-lasting neurocognitive problems including learning and memory impairments and an anxious phenotype. Because millions of children each year undergo procedures that require anaesthesia, it is important to investigate ways to protect the vulnerable developing brain. We evaluated whether progesterone treatment administered before general anaesthesia exposure could prevent long-term anaesthesia-induced neurocognitive and behavioural changes. Methods: Female and male Long–Evans rat pups were repeatedly exposed to 2 h of sevoflurane or control procedures at postnatal days 7, 10, and 13. Subcutaneous injections of progesterone or vehicle were administered immediately before general anaesthesia exposure or control procedures. Neurobehavioural and cognitive outcomes were evaluated using elevated plus maze and Morris water maze tests. Results: Prophylactic progesterone treatment attenuated the chemokine (C-X-C motif) ligand 1 (CXCL1) response to sevoflurane exposure. Rats given vehicle treatment with general anaesthesia exposure exhibited increased anxiety on the elevated plus maze and learning and memory impairments on the Morris water maze. However, rats treated with progesterone before general anaesthesia lacked these impairments and performed in a similar manner to controls on both tasks. Conclusions: Progesterone attenuated the anaesthesia-induced, acute peripheral inflammatory response and prevented cognitive and behavioural alterations associated with early repeated general anaesthesia exposure. Importantly, our results suggest that progesterone treatments given before general anaesthesia may help to protect the developing brain.